Operational reliability enhancement with PMUs in indian power network - Pandey R.K.; Pentayya P.; Gartia A.; Rajkumar A.; Kumar C. (My University, 2025)
This paper presents the operational improvements of power network with deployment of Phasor Measurement Units (PMUs). PMUs are newly emerged tools for monitoring the grid parameters and thus help system operator in quickly identifying the stressed areas and take remedial actions. This has been proved as suitable sensory device for immensely improving the situational awareness among system operators. In India, Synchrophasor technology is in its initial stages with lots of pilot/demo projects undergoing. Still at nascent stage of implementation also, this has shown immense potential benefits and is being used by the system operators for reliable operation of grid. The paper provides Indian utility experience of PMUs usage in evolving power systems. Also, the paradigm shift from the conventional SCADA system to Wide area measurement system in India has been adequately addressed. © 2013 IEEE.